ANALISIS NILAI TAMBAH KERIPIK TALAS PRIANGAN PADA âINDUSTRI RUMAH TANGGA DARMATIAN PRODUCTâ DI KOTA PALU - Harnum, Harnum (AGROTEKBIS, 2016)
This study aims to determine how much added value on taro which has been processing into chips. Determination of the respondents in this studywas done by intentionally (purposive). Respondents who selected was the chief of "Darmatian Product". Tarigan method was used to analysis the value added. The results showed that the home industry of "Darmatian Product" got benefits 6,667,476.16, this got from 8 times of processing for September 2016 and the valued added was10,436.73 perkilogram of raw material used.Key Words: Home Industry Darmatian Product, Value Added, Taro Chips.